Crises et transformations du modèle social-démocrate suédois - Jean-François Vidal (Revue de la Régulation)
This article presents an analysis of the causes and outcomes of the crisis of the Swedish model. We begin by describing the principal features of the Social-Democratic policies that were implemented between the 1930’s and the 1970’s. Next, we discuss the possible causes of the economic slump between from the 1970’s through the 1990’s. We conclude that the severe financial crisis of 1991-1992 that followed bank deregulation played a more significant role than did the erosion of the neo-corporatist collective bargaining system, the expansion of the welfare state, or the inadequacy of the specialization of the country’s exports. In order to reduce the considerable public deficit caused by the recession, the government implemented a strict austerity program that included cuts in expenditures an proportionate tax increases. Despite the severity of these policies, the Swedish welfare state remains extensive. Ultimately, the growth regime (in the regulationist sense) was rapidly transformed following the crisis. Subsequent growth resulted primarily from an increase in the nation’s share of world exports and an increase in the foreign trade surplus (neo-mercantilist growth), in turn principally due to the krona’s depreciation and the compression of domestic demand due to the relatively traditional specialization of exports.